HUMAN CAPITAL DEVELOPMENT AND ORGANIZATIONAL PERFORMANCE: A FOCUS ON ISLAMIC PERSPECTIVE - Abdul Ghani Azmi, Ilhaamie (Jurnal Syariah, 2009)
In Islam, the objective of human capital development is not only to produce a better person in terms of possessing technical knowledge, skills and good values but also a person with a better soul. This is because in Islam, a better person is a person who does not only possess the worldly knowledge, skills and Islamic values but most importantly practices them. Consequently, he or she will be a good worker that will not act in his or her own interests but to be loyal to his or her employer as he or she is fearful (taqwa) of Allah the Al-Mighty. Hence, human capital development from Islamic perspective focuses on purifying one’s soul (tazkiyah al-nafs), instilling Islamic values (al-ta’dib), understanding the philosophies of Allah’s Oneness and Greatness (altawhid al-uluhiyyah and al-rububiyyah) and the concepts of working as a vicegerent (khalifah), a team (jama’ah), full submission to Allah (‘ibadah) and a way to succeed (al-falah). Islamic human capital development also stresses on the importance of knowledge, physical development and the trainers themselves. In this respect, the teaching of Islam highlighted several important approaches to rationalize the concepts. They are, for example; through sermons (tadhkirah), discussion of the Islamic principles in view of al-Qur’an and al-Hadith (Prophet’s prescriptions) and congregational prayers. Human capital development in conventional perspective, however; is concentrated more on upgrading knowledge and skills. Good values are inculcated informally through teamwork, ceremonies, training etc. but with less focus on religious aspects. Therefore, human capital development from Islamic perspective suggested an integrated and comprehensive solution compared to the conventional perspective. As a result, the organization will be able to perform better due to the maximum productivity and profitability gained from quality services rendered by the personnel or workers.